Masyarakat Siaga Dan Tanggap Bencana Banjir - Erman Syarif; Hendra Hendra; Maddatuang M; Alief Saputro (Universitas Negeri Gorontalo, 2022)
The flood has caused considerable material loss. This PKM activity aims to: 1) increase public knowledge about the importance of early detection of flood disasters, 2) provide training on flood disaster management to the community, 3) create awareness about how flood disasters work, and 4) create a community culture that is prepared and responsive to flood disasters. Implementation of PKM in Sapanan Village, Binamu District, Jeneponto Regency on September 24 2022. The method used for this activity is the lecture and discussion method. PKM activities carried out in Sapanan Village, Binamu District, Jeneponto Regency have made a positive contribution to community knowledge about the importance of early detection of flood disasters, provided training on flood disaster management to the community, created awareness about how flood disasters work, and created a culture of community that is prepared and responsive to disasters flood.